ANALISIS YURIDIS TERHADAP WANPRESTASI KREDITOR SETELAH PENAMBAHAN JAMINAN DALAM PERJANJIAN KREDIT PERBANKAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1932.K/PDT/2016) - BAGINDA RACHMADSYAH HARAHAP (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Saidin3. Dedi Harianto A credit contract is a consensus agreement between a debtor and a creditor ( Bank) leading to payable accounts, in which the debtor is required to return the credit provided by the creditor, under terms and conditions approved by both parties. The research problems are how about the criteria of creditor’s default as stated in the debtor’s lawsuit concerning the implementation of the banking credit contract with addition of collateral to the total amount of the credit facility, how about the legal force of the lawsuit on default filed by the debtor against Bank Sumut as the creditor concerning the implementation of the credit contract which has been effective in line with PMK (Approval to Make Credit) No.32/KC-15/KCP-070/KAL/2011 on November 6, 2011; and how about the analysis on the ground of the Supreme Court Judges’ consideration in the Ruling No. 1932.K/Pdt/2016 in debtor’s lawsuit against creditor’s default.This is a normative juridical research which studies the prevailing laws and regulations, in this case, Law No.7/1992 in conjunction with Law No.10/1998 on Banking, Law No. 42/1999 on Fiduciary Collateral, Law No. 4/1996 on Mortgage, and the third book of the Civil Code on Contract. This is analytical descriptive which describes, explains and analyzes the problems, and finds the right answer to the problems.The research showed that one of the parties did not fully comply with the agreement in implementing the credit contract, did not completely fulfill their obligations or they did not fulfill their obligation punctually. The claim filed by debtor, RE, does not meet the elements of default since it is proved in the Court’s hearing that Bank Sumut has defaulted and the claim is considered error in personal toward the defendant. The Supreme Court Ruling has been in line with the prevailing legal provisions in a credit contract since there is no written evidence in the credit contract that requires Bank Sumut as the creditor to add the number of credit facilities when the collateral is added by the debtor.Keywords: Creditor, Debtor, Default, Credit Contract